Nutrition and Exercise Rehabilitation in Obesity hypoventilation syndrome (NERO): a pilot randomised controlled trial. Issue 1 (29th September 2017) - Mandal, Swapna; Suh, Eui-Sik; Harding, Rachel; Vaughan-France, Anna; Ramsay, Michelle; Connolly, Bronwen; Bear, Danielle E; MacLaughlin, Helen; Greenwood, Sharlene A; Polkey, Michael I; Elliott, Mark; Chen, Tao; et al.
Abstract : Background: Respiratory management of obesity hypoventilation syndrome (OHS) focusses on the control of sleep-disordered breathing rather than the treatment of obesity. Currently, there are no data from randomised trials of weight loss targeted rehabilitation programmes for patients with OHS. Intervention: A 3-month multimodal hybrid inpatient–outpatient motivation, exercise and nutrition rehabilitation programme, in addition to non invasive ventilation (NIV), would result in greater per cent weight loss compared with standard care. Methods: A single-centre pilot randomised controlled trial allocated patients to either standard care or standard care plus rehabilitation. Primary outcome was per cent weight loss at 12 months with secondary exploratory outcomes of weight loss, exercise capacity and health-related quality of life (HRQOL) at the end of the rehabilitation programme to assess the intervention effect. Results: Thirty-seven patients (11 male, 59.8±12.7 years) with a body mass index of 51.1±7.7 kg/m 2 were randomised. At 12 months, there was no between-group difference in per cent weight loss (mean difference −5.9% (95% CI −14.4% to 2.7%; p=0.17)). At 3 months, there was a greater per cent weight loss (mean difference −5% (95% CI −8.3% to −1.4%; p=0.007)), increased exercise capacity (6 min walk test 60 m (95% CI 29.5 to 214.5) vs 20 m (95% CI 11.5 to 81.3); p=0.036) and HRQL (mean difference SF-36 general health score (10 (95% CI 5 to 21.3) vs 0 (95% CI −5 to 10); p=0.02)) in the rehabilitation group. Conclusion: In patients with OHS, a 3-month comprehensive rehabilitation programme, in addition to NIV, resulted in improved weight loss, exercise capacity and QOL at the end of the rehabilitation period, but these effects were not demonstrated at 12 months, in part, due to the limited retention of patients at 12 months. Trial registration number: Pre-results; NCT01483716 .